Study design of ‘PASIBO’ - co-creation and development of a physical activity intervention to patients with inflammatory bowel disease - Tanja Thomsen; Marie Villumsen; Anja Poulsen; Anders B. G. Hansen; Bente A. Esbensen; Tine Jess; Mette Aadahl (BMC Health Services Research)
Abstract Background Patients with inflammatory bowel disease (IBD) tend to be physically inactive, i.e., not meeting the recommend daily physical activity levels, which may lead to poorer health outcomes and lower quality of life. Despite growing evidence on the benefits of physical activity, few interventions are tailored to the needs and preferences of this population. This study describes the systematic development of a co-created physical activity intervention for patients with IBD. Methods The intervention development process was guided by the Medical Research Council (MRC) framework for developing and evaluating complex interventions and informed by principles of co-creation and participatory system-oriented approaches. The process encompassed three stages, including (1) a preparation phase with e.g., literature review, stakeholder consultations and a system mapping workshop, (2) two co-creation workshops with multiple stakeholders to collaboratively design intervention components, and (3) prototyping the intervention, including reviews and feedback from health professionals and other researchers to refine content and delivery model. Results Stakeholders identified five focus areas as central to the intervention: individualization, community-fostering, mental health, sustainability, and enhancing knowledge about IBD and physical activity. The focus areas were then translated into concrete intervention elements. These included group-based educational sessions and nurse-led individual motivational counselling sessions, supplemented by optional intervention elements, consisting of one-on-one sessions with a physiotherapist, links to short videos featuring physiotherapists demonstrating specific exercises, and peer-support opportunities. During the final stage of the intervention development, feedback from a multidisciplinary team of health professionals and a researcher specializing in physical activity and IBD played a crucial role in refining and finalizing the manual’s content and practicality. Conclusions The development process resulted in a multicomponent physical activity intervention tailored to the needs and preferences of patients with IBD. The intervention integrates both individual and social components, with some optional. This intervention development highlights the value of combining evidence-based strategies with stakeholder involvement to create a contextually relevant and potentially sustainable physical activity intervention. A feasibility study currently underway will provide further insights into the feasibility and acceptability of the intervention, and the potential need for additional adjustments of intervention elements.